Raison d’agir des écologistes océaniques : du golfe de Biscaye à la mer de Patagonie - Milo Villain (VertigO)
Currently, we notice the existence of a huge and global environmental movement for the protection of the oceans. We propose the idea that its meaning can be grasped by studying the activists’ experiences, which could inform us a bit more about the modern individual subjectivity and ethic. The study has been carried out among members of environmental organizations, presenting ocean focused actions, mainly non-governmental organizations (NGOs) like Greenpeace, Sea Shepherd, or the Surfrider Foundation. The main question we try to answer is this one: “what are the motivations of these activists to get involved for the ocean?ˮ Our study shows how the activism is ruled by a logic of subjectivation, where the activists' ethic and their relationship to the world, and especially to the ocean, represent major components.